Visual participatory as an analytic tool in managing violence among students in an urban secondary school in Zimbabwe - Gudyanga, Ephias; Matamba, Nomsa (Science Publishing Group, 2016)
Publication by Ephias Gudyanga and Nomsa Matamba Midlands State University, Faculty of Education, Department of Educational Foundations, Management and Curriculum Studies